Grounding trust in inter-organizational alliances: An exploration of trust evolution - Tally Hatzakis; Rosalind Searle (Management Revue, 2006)
This paper explores the role of trust in coordinating teams operating at the interface between multiple functions and organisations in strategic alliances. To understand the issues faced by these teams, we study cognitive & relational factors between partners and focus on the process of trust evolution and risk management in the complex interface between strategic partners. This research examined two coordinating teams. We explore how coordinating teams construed risks in context; the differences of the symbolic role between formal and extra-role behaviours of partners in engendering trust; and the distinct processes through which trust was negotiated between partners. We identify the implications of trust on the management of alliances and the impact of uncertainty by exploring the role of coordinating teams in as risk mitigators, examine perceptions of trust as a coordinating mechanism, antecedent for reducing risks or just another mechanism of control, and looked at changes in partner behaviours when trust was breached. Data for this study were collected on a longitudinal basis in two case studies. The first examined a coordinating team tasked to translate an award winning innovative design into a viable museum, while the second examined a team tasked to manage the provision of outsourced insurance services offered by a financial institution. Goffman's (1972) categories of situational, relational and interpersonal risk were used as a means of framing risk and trust between stakeholder organisations and of exploring self-perceptions about their risk mitigating roles by members of the coordinating team.
Keywords: 650; resource-based view; relational view; networks; network resources; Strategische Allianz; Ressourcenorientierter Ansatz; Soziale Beziehungen